Diferensiasi Penanaman Moral Orangtua Dalam Mendidik Anak Di Wilayah Sulawesi Selatan - Afiah, Nur; Haramain, Haramain; Jafar N, Muhammad Kamil (Program Studi Sosiologi Agama Fakultas Ushuluddin, Adab dan Dakwah IAIN Manado, 2023)
Parents have an obligation to educate children through moral inculcation. Children born without morals. Moral intelligence will develop based on interactions obtained from the environment, especially the family. This quantitative research was conducted to examine differences in parents' moral instilling in educating children in four regions in South Sulawesi, namely Parepare, Barru, Sidrap, and Pinrang. The research subjects were 133 parents who had children between the ages of 6 and 12 years. The results showed that there were differences in the moral inculcation of parents in educating children in the South Sulawesi region with statistical similarities, namely (Sig) < 0.05 or (0.003) <0.05. As for the limitations of this study, there are still limited data in explaining the study of differences in moral cultivation. More in-depth research should be carried out on the model or form of moral inculcation carried out by parents in the South Sulawesi region Keywords: Differentiation, children, morality, parents